Solid-State Synthesized BiFeO3Perovskite-Based Fast-Response White-Light Photodetector - Upadhyay R.K.; Singh A.P.; Upadhyay D.; Jarwal D.K.; Kumar C.; Jit S. (My University, 2025)
This letter reports an indium doped tin oxide (ITO)/ZnO nanoparticles (NPs)/ BiFeO3 ferroelectric perovskite /poly (3, 4-ethylene dioxythiophene): polystyrene sulfonate (PEDOT: PSS)/Ag heterostructure based white-light photodetector. ZnO nanoparticles are synthesized using the sol-gel process, whereas solid-state route method is used for synthesizing BiFeO3. The X-ray diffraction (XRD) of ZnO nanoparticles and BiFeO3 thin film confirms the formation of the wurtzite hexagonal structure of ZnO NPs and the rhombohedral structure of BiFeO3 perovskite. The high-resolution scanning electron microscopy (HR-SEM) of the films confirm the highly dense and uniform growth of ZnO nanoparticles and BiFeO3. The measured responsivity characteristics over 400-750 nm show the maximum responsivity of 34 mA/W over the wavelength of 450 to 650 nm at an applied bias voltage of 2 V. The photodetector exhibits a reasonably fast light response with the rise time of 7.21 s and fall time of 6.23 s. © 1980-2012 IEEE.